Pathways to Development : Empowering local women to build a more equitable future in Vietnam - World Bank (Washington, DC, 2012)
Vietnam's economic emergence is perhaps best experienced along its rural roads: over 175,000 km of pavement, rubble and dirt track extend to two-thirds of the country's population and nearly all of the poorest people, who live among its productive farms, lush forests and meandering river valleys. The World Bank's Third Rural Transport Project (RTP3) identified missing links that left many rural Vietnamese communities off the map from the country's remarkable development successes. The project prioritized road maintenance and local infrastructure management above new construction projects, and collaborated with the government institutions to address steep increases in travel costs per kilometer across crumbling rural roads. Project staff identified barriers along the route to more accessible road networks, including a lack of incentives to local bureaucracies to regularly maintain rural roads in remote areas. This situation has lead to deteriorating roads in places that are desperate for improved access to goods, services and social networks.